Neoadjuvant Chemoradiation Followed by Radical Hysterectomy in FIGO Stage IIIB Cervical Cancer: Feasibility, Complications, and Clinical Outcome. Issue 6 (1st July 2009) - Fanfani, Francesco; Fagotti, Anna; Ferrandina, Gabriella; Raspagliesi, Francesco; Ditto, Antonino; Cerrotta, Anna Maria; Morganti, Alessio; Smaniotto, Daniela; Scambia, Giovanni
Abstract : Objective: To demonstrate the efficacy and feasibility of preoperative chemoradiation followed by radical surgery in a consecutive series of patients with stage IIIB cervical cancer. Methods: Between October 1997 and July 2007, 39 patients with International Federation of Gynecology and Obstetrics stage IIIB cervical cancer were consecutively staged and treated at the Catholic University of Rome and Campobasso and at the National Cancer Institute of Milan. Radical surgery was performed 5 to 6 weeks after the end of the cisplatinum-based neoadjuvant chemoradiation. Results: Clinical responses were observed in 35 patients (92.1%): 6 (15.8%) complete and 29 (76.3.8%) partial. Radical surgery was performed in 35 patients (89.7%). According to Chassagne classification, we observed 7 (20.0%) grade 3, 17 (48.6%) grade 2, and 28 (80%) grade 1 surgical complications. At pathological examination, 12 patients (34.3%) showed complete response, 7 patients (20.0%) had only a microscopic disease, 8 patients (22.8%) had a partial response, and the last 8 patients (22.8%) had no change in disease. We registered 11 (31.4%) operative and 4 (11.4%) early postoperative complications. Median follow-up was 33 months (range, 3-80 months). The percentages of 3-year disease-free survival and overall survival were 67.6% and 70.0%, respectively. Patients with complete response and microscopic disease showed better prognosis than patients with partial response and no change (3-year disease-free survival, 100% vs 31%; and 3-year overall survival, 100% vs 39%). Conclusions: Chemoradiation followed by radical hysterectomy could be administered in patients with stage IIIB cervical cancer with an acceptable rate of complications and with a survival outcome similar to that of chemoradiotherapy, allowing the assessment of pathological response with its implication on clinical outcomes.